Pembelajaran Keterampilan Mendengar Berbasis Video Webtoon terhadap Penguasaan Kosakata Arab Siswa Madrasah Aliyah - Ikhsan, M. Adibul; Pradibyo, Pradibyo (Study Program of Arabic Language Teaching, 2026)
This study aims to examine the effect of implementing a Webtoon-based listening learning program on students’ mastery of Arabic vocabulary at MAN 2 Banyuwangi. The research employed a quantitative, quasi-experimental design with a pretest–posttest control group. The sample consisted of 52 students selected through purposive sampling, divided into an experimental group and a control group. The research instrument was a vocabulary test administered as a pretest and posttest. Data were analyzed using descriptive and inferential statistics. The results of the normality and homogeneity tests indicated that the data did not fully meet the assumptions for parametric testing; therefore, the Mann–Whitney U test was used for hypothesis testing. The findings revealed a significant difference in vocabulary mastery between the experimental and control groups, with an Asymp. Sig. (2-tailed) value of 0.007 (< 0.05). Furthermore, the experimental group showed higher mean scores and more consistent learning outcomes compared to the control group. These results indicate that implementing a Webtoon-based Keterampilan mendengarprogram has a positive, significant effect on students’ Arabic vocabulary mastery. In conclusion, the use of digital comics (Webtoon) as a learning medium can enhance student engagement, increase reading interest, and improve vocabulary acquisition. Therefore, it can be recommended as an innovative and adaptive learning strategy in Arabic language education in the digital era.